Extracellular vesicles from adipose stem cells ameliorate allergic rhinitis in mice by immunomodulatory - Yang, Wenhan; Pan, Zhiyu; Zhang, Jiacheng; Wang, Lian; lai, Ju; Zhou, Shican; Zhang, Zhili; Fan, Kai; Deng, Dan; Gao, Zhengliang; Yu, Shaoqing (Frontiers in Immunology, 2023)
Background: Human adipose tissue-derived stem cells (hADSCs) exert potent immunosuppressive effects in the allogeneic transplantation treatment. In mouse model of allergic rhinitis (AR), ADSCs partially ameliorated AR. However, no study has evaluated the potential therapeutic effects of hADSC-derived extracellular vesicles (hADSC-EVs) on AR. Methods: Female BALB/c mice were sensitized and challenged with ovalbumin (OVA) to induce AR. One day after the last nasal drop, each group received phosphate buffered saline (PBS) or hADSC-EVs treatment. Associated symptoms and biological changes were then assessed. Results: hADSC-EV treatment significantly alleviated nasal symptoms, and reduced inflammatory infiltration. Serum levels of OVA-specific IgE, interleukin (IL)-4 and interferon (IFN)-γ were all significantly reduced. The mRNA levels of IL-4 and IFN-γ in the spleen also changed accordingly. The T helper (Th)1/Th2 cell ratio increased. The treatment efficacy index of hADSC-EV was higher than that of all human-derived MSCs in published reports on MSC treatment of AR. ADSC-EVs exhibited a greater therapeutic index in most measures when compared to our previous treatment involving ADSCs. Conclusions: These results demonstrated that hADSC-EVs could ameliorate the symptoms of AR by modulating cytokine secretion and Th1/Th2 cell balance. hADSC-EVs could potentially be a viable therapeutic strategy for AR. Further animal studies are needed to elucidate the underlying mechanisms and to optimize potential clinical protocols.